Writing about Smart Cities in Indonesia: A Bibliometric Analysis - Anang Dwi Santoso; Januar Eko Aryansah; Annada Nasyaya (The Directorate for Research and Community Services, Institut Teknologi Bandung, 2024)
This study analyzed the development, current patterns, and main focuses in the field of smart cities in Indonesia by conducting a bibliometric analysis of 133 academic articles. The study used the Scopus database to collect data and the Bibliometrix R programme to conduct a detailed bibliometric analysis. The findings revealed a yearly rise in publications, suggesting a growing scholarly focus on smart cities. The inquiry explored the relationships between authors, their affiliations, and countries, identifying the most prominent journals and influential publications in this field. Keyword analysis revealed the main topics and subjects, which greatly aided in the strategic planning and execution of smart city projects by identifying gaps, patterns, and potential areas for further investigation. This bibliometric analysis provides detailed insight into the study on smart cities in Indonesia, showing a transition from an initial emphasis on technology and sustainability to a wider range of sustainable development and sociological aspects. The findings emphasize the need for interdisciplinary approaches and increased regional and international partnerships to tackle complex urban challenges. This study promotes a holistic view of the smart city that combines technological advancement with community involvement and urban quality of life.